THE EFFECTIVENESS OF HEALTH EDUCATION THROUGH E-FILES MULTIMEDIA AND FACE-TO-FACE CLASSROOM LEARNING ON ADOLESCENTS’ REPRODUCTIVE HEALTH KNOWLEDGE AMONG SEVENTH-GRADE STUDENTS AT SMPN 1 KRAMATWATU, SERANG, BANTEN - Ika Apriyanti; Nuria Fitri Adista (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2026)
Background : Adolescence is a transitional period between childhood and adulthood. During this time, many changes occur in adolescents, including physical changes, puberty, and behavior. Globally, health issues among adolescents are primarily driven by risky behaviors such as unhealthy dating, smoking, alcohol consumption, and drug use, which have become major concerns worldwide. This research aims to prove the influence of Health Education through Multimedia E-Files and Face-to-Face Learning in the Classroom on Adolescent Reproductive Health Knowledge. Methods: The research design is a Quasi-Experimental Design with a pretest-posttest control group design. The sample consists of seventh-grade students from SMP Negeri 1 Kramatwatu, with 45 respondents in the control group and 45 respondents in the experimental group, using probability sampling with proportional random sampling method. Data analysis was conducted using Wilcoxon and Mann-Whitney tests. Results: Indicate an effect of reproductive health education through E-File Multimedia media on adolescents' reproductive health knowledge. The average N-Gain Score in the control group was 31.33, while in the experimental group, it was 59.34. Conclusion : Future research is expected to implement different interventions regarding the TRIAD KRR in adolescents and enhance the effectiveness of other media or expand this research with different variables to provide the latest innovations in health education.